Journal of Cannabis Research - Gorelick, David A.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The Journal of Cannabis Research is an international, fully open-access, peer-reviewed journal which welcomes submissions covering all topics pertaining to cannabis. Sponsored by the Institute of Cannabis Research at Colorado State University-Pueblo. The Journal publishes a broad range of articles including, but not limited to: the agriculture, plant biology, and commercial and industrial uses of the cannabis plant (including non-psychoactive varieties such as hemp) and its constituents; the endocannabinoid system; the preclinical and clinical pharmacology and toxicology of cannabis and cannabinoids; epidemiology and public health aspects and social impacts of cannabis use and cannabis-related disorders; prevention, screening, diagnosis, and treatment of cannabis-related disorders; therapeutic uses of cannabis and cannabinoids in humans and animals; business, economic, and environmental aspects of the cannabis industry; and historical, public policy, legal, ethical, and international aspects of cannabis. The Journal of Cannabis Research welcomes original research articles and brief reports, study protocols, narrative and systematic reviews and meta-analyses, technical notes, commentaries and perspectives, conference reports, case reports, and letters to the editor. Submission enquiries are welcomed for manuscripts that fall outside these classifications; contact information can be found at the bottom of this page. Cannabinoids are broadly defined as comprising all constituents of the cannabis plant (phytocannabinoids, terpenes, and flavonoids) as well as synthetic cannabinoids. The Journal of Cannabis Research is the leading outlet for cannabis research globally, as well as one of few that are fully open access and is the only broad, interdisciplinary cannabis journal. Its intended audience is not only clinicians and biological scientists, but also social scientists, lawyers, economists, business experts, ethicists, public policy experts, and public officials. The goal is to provide an outlet for experts across disciplines and foster innovation and collaboration, driving public and scientific discourse around this timely issue and furthering this exciting area of research. The open access nature of the journal ensures that authoritative and accurate information pertaining to all aspects of cannabis is available to both the academic community and public policy makers in a timely manner. The Journal is firmly committed to scientific and publication ethics. It adheres to Committee on Publication Ethics (COPE) guidelines and does not publish work that does not meet accepted legal, regulatory, and professional standards for human and animal protection, avoidance of conflict of interest (both financial and intellectual), and plagiarism. The Editor-in-Chief is supported by a distinguished Editorial Board of leading researchers and investigators, with expertise covering the full breadth of the journal's scope.
Keywords: Public health; Psychiatry; Medical sciences; Drug development; Plant genetics; Neuropharmacology; Agriculture; Public Health; Psychiatry; Preclinical Research; Plant Genetics; Neuropharmacology; Agriculture